2011 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2011
DOI: 10.1109/iembs.2011.6091797
|View full text |Cite
|
Sign up to set email alerts
|

Artificial neural network based intracranial pressure mean forecast algorithm for medical decision support

Abstract: Although the future mean of intracranial pressure (ICP) is of critical concern of many clinicians for timely medical treatment, the problem of forecasting the future ICP mean has not been addressed yet. In this paper, we present a nonlinear autoregressive with exogenous input artificial neural network based mean forecast algorithm (ANN(NARX)-MFA) to predict the ICP mean of the future windows based on features extracted from past windows and segmented sub-windows. We compare its performance with nonlinear autor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…In 2011, Zhang and associates 49 described a non-linear autoregressive with exogenous input artificial neural network-based mean forecast algorithm (ANN NARX -MFA) to predict ICP. This algorithm, which extracted features from past windows and segmented sub-windows for processing, was shown to be superior (15-min coefficient of determination [R 2 ] 0.93 ± 0.05 and relative absolute error [RAE] 9% ± 3%) to an ANN NAR algorithm (15-min R 2 0.88 ± 0.07 and RAE 15% ± 5%), which did not incorporate feature extraction.…”
Section: Icp Forecasting Algorithmsmentioning
confidence: 99%
See 3 more Smart Citations
“…In 2011, Zhang and associates 49 described a non-linear autoregressive with exogenous input artificial neural network-based mean forecast algorithm (ANN NARX -MFA) to predict ICP. This algorithm, which extracted features from past windows and segmented sub-windows for processing, was shown to be superior (15-min coefficient of determination [R 2 ] 0.93 ± 0.05 and relative absolute error [RAE] 9% ± 3%) to an ANN NAR algorithm (15-min R 2 0.88 ± 0.07 and RAE 15% ± 5%), which did not incorporate feature extraction.…”
Section: Icp Forecasting Algorithmsmentioning
confidence: 99%
“…This algorithm, which extracted features from past windows and segmented sub-windows for processing, was shown to be superior (15-min coefficient of determination [R 2 ] 0.93 ± 0.05 and relative absolute error [RAE] 9% ± 3%) to an ANN NAR algorithm (15-min R 2 0.88 ± 0.07 and RAE 15% ± 5%), which did not incorporate feature extraction. 49 In a 2012 follow-up study by the same group, Feng and co-workers demonstrated that a forecasting model utilizing temporal information on historical ICP readings and related parameters (MAP, pressure reactivity index [PRx], and brain tissue oxygenation [P bt O 2 ]) improved forecasting performance by an average of 20% ( p -value <0.001) compared with algorithms that did not make use of such information. 50 …”
Section: Icp Forecasting Algorithmsmentioning
confidence: 99%
See 2 more Smart Citations
“…It uses simple features such as the last measured ICP value or the time to the last ICH crisis. Besides tackling the classification task directly, other models have been suggested that predict the future ICP mean value, for example by using nearest-neighbor regression (Bonds et al 2015b), neural networks (Shieh et al 2004, Zhang et al 2011 or ARIMA models (Zhang et al 2012).…”
Section: Related Workmentioning
confidence: 99%